On the desirability of taxing charitable contributions - Tomer Blumkin; Efraim Sadka (Center for Economic Studies and ifo Institute (CESifo), 2007)
We develop a model that allows for public goods and status signaling through charitable contributions. This model provides a unified framework in which contributions are driven both by altruism and status signaling. We use this setup to re-examine the conventional practice of rendering a favorable tax treatment to charitable contributions.
Keywords: H2; D6; 330; Spende; Steuerbegünstigung; Öffentliches Gut; Optimale Besteuerung; Altruismus; Sozialer Status; Signalling; Verteilungswirkung; Theorie